ミズホ コウゲン ニシ エンダービーランド セッピョウ ソウ ノ チキュウ カガクテキ ケンキュウ - 室住, 正世; ムロズミ, マサヨ; MUROZUMI, Masayo (国立極地研究所, 1975)
P(論文) Chemical features and profiles of ice sheets in Mizuho Plateau and West Enderby Land have been revealed by means of newly developed analytical techniques such as atomic absorption spectrophotometry and isotope dilution mass-spectrometry. The chemical concentration is at the level of only ppb even for the major components, Na, K, Ca and Mg, chemical properties being homogeneous in the surface sheet but of much vertical complexity. Silicate dusts which functioned as the condensation nuclei for the formation of snow flakes are poor, while sea salts account for more than 90 percent of the total weight of components. Annual accumulation of chemical components, μg/cm^2, is 0.1 for silicate dusts and 0.40, 0.03, 0.1 and 0.06 for Na, K, Mg and Ca originating in the latter source. departmental bulletin paper